Influence of the Methane–Zeolite a Interaction Potential on the Concentration Dependence of Self-Diffusivity - Chaitanya A. Krishna; Subramanian Yashonath; Andreas Schüring; Siegfried Fritzsche; Jörg Kärger (Adsorption Science & Technology)
Studies on the diffusion of methane in a zeolite structure type LTA (as per IZA nomenclature) have indicated that different types of methane–zeolite potentials exist in the literature in which methane is treated within the united-atom model. One set of potentials, referred to as model A, has a methane oxygen diameter of 3.14 Å, while another set of potential parameters, model B, employs a larger value of 3.46 Å. Fritzsche and co-workers (1993) have shown that these two potentials lead to two distinctly different energetic barriers for the passage of methane through the eight-ring window in the cation-free form of zeolite A. Here, we compute the variation of the self-diffusivity (D) with loading (c) for these two types of potentials and show that this slight variation in the diameter changes the concentration dependence qualitatively: thus, D decreases monotonically with c for model A, while D increases and goes through a maximum before finally decreasing for model B. This effect and the surprising congruence of the diffusion coefficients for both models at high loadings is examined in detail at the molecular level. Simulations for different temperatures reveal the Arrhenius behaviour of the self-diffusion coefficient. The apparent activation energy is found to vary with the loading. We conclude that beside the cage-to-cage jumps, which are essential for the migration of the guest molecules, at high concentrations migration within the cage and guest–guest interactions with other molecules become increasingly dominant influences on the diffusion coefficient and make the guest–zeolite interaction less important for both model A and model B.